Language Learning Strategies Use And Challenges Faced By Adult Arab Learners Of Finnish As A Second Language In Finland - Ahmed H. Naif; Noor Saazai Mat Saad (Canadian Center of Science and Education, 2024)
Non-Indexed Publication